Investigation of the activity of transposable elements and genes involved in their silencing in the newt Cynops orientalis, a species with a giant genome - Federica Carducci (Nature Portfolio, 2021)
Abstract Caudata is an order of amphibians with great variation in genome size, which can reach enormous dimensions in salamanders. In this work, we analysed the activity of transposable elements (TEs) in the transcriptomes obtained from female and male gonads of the Chinese fire-bellied newt, Cynops orientalis, a species with a genome about 12-fold larger than the human genome. We also compared these data with genomes of two basal sarcopterygians, coelacanth and lungfish. In the newt our findings highlighted a major impact of non-LTR retroelements and a greater total TE activity compared to the lungfish Protopterus annectens, an organism also characterized by a giant genome. This difference in TE activity might be due to the presence of young copies in newt in agreement also with the increase in the genome size, an event that occurred independently and later than lungfish. Moreover, the activity of 33 target genes encoding proteins involved in the TE host silencing mechanisms, such as Ago/Piwi and NuRD complex, was evaluated and compared between the three species analysed. These data revealed high transcriptional levels of the target genes in both newt and lungfish and confirmed the activity of NuRD complex genes in adults. Finally, phylogenetic analyses performed on PRDM9 and TRIM28 allowed increasing knowledge about the evolution of these two key genes of the NuRD complex silencing mechanism in vertebrates. Our results confirmed that the gigantism of the newt genomes may be attributed to the activity and accumulation of TEs.